Turk xalq to’y marosimlarida qizil rangning ramziy ma’nolari - Selma Ozan Yujel qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article is dedicated to the uniqueness of Turkish folk wedding ceremonies and the symbolic expression of red color. The symbolic meaning of the red color found in the wedding ceremony are explained as examples.